Disinfection of rice using ozone treatment - Abdul Karim Shah, Nor Nadiah (2009)
The main objectives of this study are 1) to determine the effect of different ozone concentrations and exposure times for Sitophilus oryzae in milled rice in terms of mortality and survivality rates, 2) to investigate the effect of different ozone concentrations and exposure times for reducing pathogenic Bacillus cereus in rice and 3) to evaluate the changes in physicochemical characteristics of rice exposed to different ozone treatments (pH, color, moisture content, cooking quality, total solids, hardness of uncooked and cooked rice, adhesiveness of cooked rice and sensory evaluation). Ozonation treatment was done in various concentrations (0.1, 0.2, 0.3 and 0.4 ppm) and exposure times (0, 60, 120, 180, 240, 300, 360 and 420 minutes). One hundred gram of white milled rice samples were ozonated in a gas tight lieberg condenser (56 x 2.5 cm diameter) placed in an air conditioned room of 20°C ± 3°C, and 50% relative humidity. The glass condenser was connected to an ozone generator (Model OM-1, Top Ozone,Malaysia) in which ozone was produced from the ambient air. In order to generate commercial levels of ozone, corona discharge method is used in this type of ozonator. After sample was subjected to ozone treatment, it was removed and tested before being stored in polyethylene bag at room temperature before sensory evaluation tests take place. From the results obtained for the mortality rate of Sitophilus oryzae L., there is a significant difference (P<0.05) between the maximum exposure times and control, nonozonated rice samples. It was shown that at 360 minutes of 0.3 ppm ozone exposure to be the minimum lethal limit of Sitophilus oryzae L. This result also applies to the survival rate of Sitophilus oryzae L., where it was found to decrease sharply even when the lowest dosage (0.1 ppm) of ozone level was hosed to the rice samples (P < 0.05). At ozone concentration of 0.3 ppm and 360 minutes, no rice weevils emerged after a month. These results proved that ozone is lethal to Sitophilus oryzae L. at or above 0.3 ppm of ozone concentrations which would be potent to eliminate all rice weevils in rice. Ozonation treatments on Bacillus cereus have shown positive results, where all of ozone concentrations gave a significant difference (P < 0.05) on Bacillus cereus counts. Significant trends were observed in comparison with the non-ozonated rice samples. Non-ozonated rice samples were found with an average of 5.50 ± 0.28 log count (cfug-1). At 0.1 ppm, the minimum value of Bacillus cereus were found with 5.20 ± 0.02 log count (cfug-1) at 420 minutes of ozone exposure. Meanwhile, 4.84 ± 0.03 log count of Bacillus cereus were found in 0.2 ppm at 420 minutes. Up to 1.63 log reductions of Bacillus cereus counts were observed above 0.3 ppm ozone concentration at the end of 420 minutes of treatment. Bacillus cereus counts were shown to decrease to 3.62 ± 0.38 log count (cfug-1) at 0.4 ppm ozone concentration after 420 minutes of ozone treatment. These results shown a maximum reduction of 31% of Bacillus cereus count when ozone of 0.4 ppm was exposed to white milled rice. Physicochemical tests were done to see the effect of ozonation treatment towards pH,color, moisture content, cooking quality, total solids, hardness of uncooked and cookedrice and adhesiveness of cooked rice. Results have shown that moisture content, adhesiveness of cooked rice and hardness of uncooked rice have no significant changes (P > 0.05) in comparison with non - ozonated rice. Meanwhile, color, pH, total solids and cooking quality results have shown significant changes (P < 0.05) than non -ozonated rice samples. These analyses proved that there are limitations to how much ozone concentration and exposure times that can be exposed to rice without causing any detrimental effects on the physicochemical properties of rice. As a conclusion, ozone has effectively shown its anti-microbial and fumigation characteristics that are invaluable in food industry, where effective applications to ensure safer food products are highly prioritize. Based on this study, sound advantages of ozone applications can be seen on rice. Even though, it does not leave any residue due to quick decomposition of its structure, restrictions should be applied through limitation of ozone concentrations or exposure times.